Peningkatan Cakupan Imunisasi Bayi dan Balita dengan Pendekatan Penyuluhan Terfokusdi Desa Seminar Salit Kec. Brang Rea Kabupaten Sumbawa Barat - Nilawan, Nilawan; Makmun, Indriyani (FKM UIN Sumatera Utara Medan, 2023)
Immunizations are mandatory for babies aged 0-9 months. Immunization is an attempt to actively induce or enhance a person's immunity to a disease or an attempt to provide immunity to infants and children by injecting vaccines into the body to stimulate the production of antibodies aimed at preventing certain diseases. Counseling is an activity of educating something to individuals or groups, providing knowledge, information and various abilities so that they can shape the attitudes and behavior of life that should be. In essence, counseling is a non-formal activity in order to change society towards a better condition as aspired to. The purpose of this counseling is to increase the awareness of mothers who have babies under five to carry out immunizations for their babies and toddlers. The methods used include lectures/delivery of material as well as questions and answers to support mothers' knowledge about immunization in infants and toddlers. The results of KKN activities are proven by the activeness of the participants in this activity, the implementation of the activities has been able to increase the mother's knowledge and is willing to give immunizations to her child.